Psychological Factors Influencing Teacher Job Satisfaction: A Case Study at Persatuan Islam 40 Sarongge Islamic Boarding School - Anisa Siti Hodijah; Mulyawan Safwandy Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to explore the influence of psychological factors on teachers' job satisfaction at Pesantren Persatuan Islam 40 Sarongge. The background of this study focuses on the importance of teachers' roles in education and how their psychological conditions can affect job satisfaction. This research identifies the challenges teachers face, including a lack of motivation and support in the work environment, as well as the impact of technological changes on the teaching methods they use. The method used was a quantitative approach with data collection through a survey involving teachers in the pesantren. The data obtained were analyzed using statistical techniques to determine the relationship between psychological factors and job satisfaction. The results showed that there was a significant influence of psychological factors, such as intrinsic motivation and environmental support, on teachers' job satisfaction. Teachers who are highly motivated and feel supported tend to be more satisfied with their jobs. The findings emphasize the importance of creating a supportive work environment to increase teacher job satisfaction in educational institutions.